From Penang to Jakarta: competing in the Al TEACH for ASEAN Hackathon / Muhammad Aiman Abdul Halim - Abdul Halim, Muhammad Aiman (Academy of Language Studies, 2025)
I am very thankful for the opportunity to join the 2-day 'Microsoft Al TEACH Train the Trainers' held virtually from 14th to 15th August 2024. involving around 200 lecturers from UiTM Cawangan Pulau Pinang. During this session, we were introduced to the application of generative Al. ethical considerations in Al use. and practical usage of several Microsoft Al tools. Being fascinated by technology. I enjoyed the process and participated actively in all activities. One notable activity involved integrating Al into our current educational practices. My team was tasked with integrating ethical Al use. and I led the discussion, proposing a solution that combined UiTM's ADAB Model with Microsoft's six principles of responsible Al. Presenting our ideas to all participants and receiving positive feedback from the facilitators was a highlight for me.